Peramalan Tren Pencarian Kata Kunci “Sarung Wadimor” Di Indonesia Pada Data Google Trends Menggunakan Time Series Regression with Calender Variation dan Arima Box-Jenkins - Andrea Tri Dani; Meirinda Fauziyah; Hardina Sandariria (Department of Mathematics, Hasanuddin University, 2023)
The impact of this 4.0 era is that data is growing and can be collected very easily and then reprocessed to obtain information. One of the search engines for various data and information that is often used is Google, causing a high search intensity and will further impact on increasing the amount of data generated by search engines. Google Trends is one of the official websites from Google that reflects or takes pictures of events in society based on search keywords. The search keyword that will be studied in this article is “Sarung Wadimor”. Therefore, the purpose of this research is to forecast the search trend for the keyword